Anthropometric aspects of the human skeleton - Grzegorz Wróbel; Jakub Spałek; Paweł Zieliński (Kazimierz Wielki University, 2017)
The anatomy deals with learning about the shape and structure of the human body, and at the same time it is the basis for all sciences whose scope of interest relates to the human body. Anthropometric studies are aimed at translating the size and shapes of the human body into specific numbers and quantitative ratios, thus they constitute a set of measurement techniques and methods, through which it is possible to closely examine the diversity of human measurable features as well as variability in individual and evolutionary development. The scope of measurements in anthropometry applies mainly to sections, circumferences, angles between planes or body lines. The aim of the work is to present selected anatomical features of the human skeleton in the aspect of sexual dimorphism and individual human variability